Extensive grazing as a tool for building socio-ecological resilience in fire-prone territories: Insights from The Valencian Region, Spain - Calero Valdez, Diego (2023)
Wildfires are part of the socio-ecological history of fire-prone territories such as Mediterranean Europe. However, during the las decades, the increasing severity of wildfires due to socio-environmental factors have revealed the vulnerability of these socio-ecological systems (SESs) in the face of global environmental change, revealing the need to increase resilience in the face of wildfires. In contrast to the well stablished wildfire suppression policies, which in the long term have resulted in fuel build-up and larger wildfires, increasing literature suggest focussing on wildfire prevention. Among the potential measures, fostering extensive grazing is on strategy that is gaining visibility in fire-prone territories such as Spain, where the activity has been traditionally carried out but currently is showing an abandonment tendency. Widespread research has been done on the ecological function that extensive grazing has in preventing wildfires by regulating the structure and composition of the vegetation. However, little is known about how, from a socio-politically perspective, this activity contributes to build socio-ecological resilience (SER). Therefore, this study aims to contribute to shorten this knowledge gap by exploring the highly fire-prone region of Valencia (Spain), examining the socio-ecological aspects of extensive grazing using the SES framework as a starting point, analysing the interactions between its coupled social and ecological dimensions, and exploring how extensive grazing contributes to the construction of SER in the face of wildfires by applying a socio-politically sensitive framework. To do so, a qualitative approach was followed, and the information was gathered through both literature review and interviews. The findings of this investigation evidence that extensive grazing contributes in several aspects to socio-ecological resilience in the face of wildfires in the study area. Due to its territorial importance, the development of a governance system that foster extensive grazing to contribute to wildfire prevention has been promoted. However, an inclusive governance structure for the involvement and participation of rural actors, such as extensive herders is still lacking. Nevertheless, local initiatives have managed to position themselves in the territory to demonstrate the work of extensive grazing and its importance for the SES, building SER through its intervention, taking advantage of the windows of opportunity wildfires have provided to recover the local socio-ecological knowledge, to revalue the role of extensive grazing and to foster collaboration with the governmental authorities.